Supply Chain Resilience Roadmaps for Major Disruptions - Jessica Olivares-Aguila; Alejandro Vital-Soto (Logistics, 2021)
Background: Unexpected events or major supply chain disruptions have demonstrated the vulnerability in which supply chains operate. While supply chains are usually prepared for operational disruptions, unexpected or black swan events are widely disregarded, as there is no reliable way to forecast them. However, this kind of event could rapidly and seriously deteriorate supply chain performance, and ignoring that possibility could lead to devastating consequences. Methods: In this paper, definitions of major disruptions and the methods to cope with them are studied. Additionally, a methodology to develop supply chain resilience roadmaps is conceptualised by analysing existing literature to help plan for unexpected events. Results: The methodology is introduced to create roadmaps comprises several stages, including supply chain exploration, scenario planning, system analysis, definition of strategies, and signal monitoring. Each roadmap contains the description of a plausible future in terms of supply chain disruptions and the strategies to implement to help mitigate negative impacts. Conclusions: The creation of roadmaps calls for an anticipatory mindset from all members along the supply chain. The roadmaps development establishes the foundations for a holistic supply chain disruption preparation and analysis.